Surface Whiskerization Of Carbon Fibers With Carbon Nanotubes - Jones @ John Vargis, Christina Vargis (2007)

(untitled)
Carbon fibers are the main reinforcing fibers used in high performance polymer matrix composites in various applications such as manufacturing of aerospace vehicles and high quality sports gear. Composite performance can be enhanced by applying an optimum level of fiber surface treatment. Surface treatments may be classified into oxidative and non-oxidative treatments. In this study, whiskerization which is a type of non-oxidative treatment was employed. This treatment involved the coating of untreated carbon fibers with carbon nanotubes (CNTs). There are three main objectives in this study. The first objective was to design and fabricate a chemical vapour deposition (CVD) reactor system that enables the growth of CNTs from carbon fiber surface. The second objective was to carry out whiskerization treatment at various conditions and to characterize the CNT-coated fibers at these conditions. Characterization of CNT-coated fibers was conducted at varying regions within the reaction tube; at reaction temperatures between 800-1000oC and carrier gas (hydrogen) flow rates between 100-500ml/min. Characterization of the CNTs formed on the carbon fibers was also conducted. The third objective was to investigate the flexural properties of composites made from untreated and CNT-coated carbon fibers. A CVD reactor system, referred to as CVD rig was successfully designed and fabricated to grow CNTs on untreated carbon fiber. CNTs grew on carbon fiber at region 1 for all treatment conditions. The CNTs grown on the carbon fibers increased in length and distinctness of parallel graphitic sheets alignment as the reaction temperature increased from 800 to 1000oC. As the hydrogen flow rate increased from 100 to 500 ml/min, the CNT coatings on the fibers were relatively more even and the amorphous carbon impurities (indicated by clumps) on the CNT-coated fibers disappeared (only observed at 800oC). “Whisker-like” morphology and bi-directional growth were the two types of CNT conformations produced in this study. The CNTs grown was identified as multi-walled carbon nanotubes (MWCNTs). Whiskerization treatment on carbon fibers increases the flexural strength of composites between 44-122%. Higher reaction temperature and hydrogen flow rate during carbon fiber whiskerization treatment lowers the flexural strength of its composite. Hydrogen flow rate has lesser impact on the flexural strength as compared to the reaction temperature. Observation of carbon fiber-epoxy composite fracture surface indicated CNT-coated carbon fiber bonds better with epoxy matrix compared to untreated carbon fiber.